P09.03 Cathepsin S alterations induce a tumor-promoting immune microenvironment in follicular lymphoma. (1st October 2020) - Hildebrand, JA; Bararia, D; Stolz, S; Häbe, S; Osorio-Barrios, F; Bartoschek, MD; Gaitzsch, E; Jurinovic, V; Rautter, K; Ludwig, C; Bultmann, S; Leonhardt, H; et al.
Abstract : Background: By targeted DNA sequencing of 305 diagnostic follicular lymphoma (FL) biopsies, we identified somatic mutations of Cathepsin S (CTSS) in 8% of cases (24/305), mostly clustered at Y132 (19/24) converting Y to D (16/19). Another 13% of FL had CTSS amplifications (37/286), associated with higher CTSS expression ( P= 0.05 ). CTSS is a cysteine protease that is highly expressed in endolysosomes of antigen presenting cells and malignant B-cells. CTSS is involved in proteolytical processing of antigenic peptides for presentation on MHC-II to be recognized by antigen specific CD4 + T-cells. 1 CTSS is synthesized as an inactive zymogen, which is converted to its active form by autocatalytic cleavage of the autoinhibitory propeptide (pro-CTSS). Materials and Methods: We used CRISPR/Cas9 to introduce CTSS Y132D into Karpas422, a B-cell lymphoma cell line that harbors the FL hallmark translocation t(14;18). We purified pro-CTSS WT and Y132D and assayed the in vitro autocatalytic cleavage over time. We then tested the impact of CTSS on CD4 + T-cell activation in co-culture assays, in a previously described in vivo model 2 which we slightly modified to reflect FL-like conditions, and in primary patient samples. Results: Single-cell derived Y132D mutant Karpas422 clones showed >3-fold higher ratios of active CTSS to pro-CTSS (N=4, P= 0.0003 ). Immunoprecipitated CTSS Y132D had >3-fold higher in vitro substrate cleavage activity compared to CTSS wild type (WT) (N=6, P= 0.001 ) which was mediated by an accelerated conversion from pro-CTSS to active CTSS (11 minutes for CTSS Y132D vs 17 minutes for CTSS WT; N=3, P =0.04). Molecular dynamics simulations showed that the Y132D mutation shortens the distances by ~2Å between the catalytic triad of active CTSS (C139, H278, N298) and a stretch of amino acids from the proform (L80, G81, D82, S94), which could facilitate intramolecular cleavage. The higher substrate cleavage activity of CTSS Y132D came along with a high capacity to stimulate antigen specific CD4 + T cell responses in vitro and in vivo . Additionally, CTSS overexpression could phenocopy this high CD4 + T cell activation. Lastly, we aimed to correlate CTSS aberrations with clinical outcome in patients who received standard immunochemotherapy (R-CHOP) for advanced FL (N=51 with available CTSS mutation and gene expression data). Compared to all other patients (N=34), patients with CTSS Y132 mutations or CTSS overexpression (N=17) had longer failure free survival ( P =0.012). Conclusions: Here, we provide biochemical, structural, functional and clinical evidence that aberrant CTSS activity induces a supportive immune microenvironment in FL. We propose that aberrant CTSS activity can elicit a CD4 + T-cell driven tumor-promoting immune response, which could be amplified within the microenvironment and substantially impact the biology and clinical course of the disease. Thus, aberrant CTSS activity is a promising biomarker and therapeutic target in FL and potentially also other tumors. References: Riese, R.J., et al ., Essential role for cathepsin S in MHC class II-associated invariant chain processing and peptide loading. Immunity 1996; 4 (4): p. 357–66. Kim, K.J., et al ., Establishment and characterization of BALB/c lymphoma lines with B cell properties. J Immunol 1979; 122 (2): p. 549–54. Disclosure Information: J.A. Hildebrand: None. D. Bararia: None. S. Stolz: None. S. Häbe: None. F. Osorio-Barrios: None. M.D. Bartoschek: None. E. Gaitzsch: None. V. Jurinovic: None. K. Rautter: None. C. Ludwig: None. S. Bultmann: None. H. Leonhardt: None. S. Eustermann: None. K. Hopfner: None. W. Hiddemann: None. M. Bergwelt: None. M. Schmidt-Supprian: None. M.B. Sárosi: None. M. Rudelius: None. V. Passerini: None. J. Mautner: None. O. Weigert: None.